The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.3390/hydrobiology1010007
|View full text |Cite
|
Sign up to set email alerts
|

Hydrobiological Aspects of Saturated, Methyl-Branched, and Cyclic Fatty Acids Derived from Aquatic Ecosystems: Origin, Distribution, and Biological Activity

Abstract: This review focuses on the hydrobiological aspects of saturated, methyl-branched, and cyclic fatty acids (FA) derived from aquatic ecosystems. This short review presents the distribution of about 60 FA in various living organisms inhabiting the aquatic environment as well as in marine and freshwater sediments. In addition, it is important to determine the biological activity of saturated, methyl-branched, and cyclic fatty acids. An interesting finding was that some cyclic FA show antiplatelet activity. The gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 119 publications
0
1
0
Order By: Relevance
“…Several comparative studies have shown that PASS is more predictive than some other recently developed methods for assessing biological activity profiles [197,198], although this program is not sufficiently effective for complex molecules or optical isomers. To calculate the pharmacological potential profile of natural substances, we have successfully used PASS for the past fifteen years [200][201][202][203][204][205].…”
Section: Structure-activity Relationships and Biological Activities O...mentioning
confidence: 99%
“…Several comparative studies have shown that PASS is more predictive than some other recently developed methods for assessing biological activity profiles [197,198], although this program is not sufficiently effective for complex molecules or optical isomers. To calculate the pharmacological potential profile of natural substances, we have successfully used PASS for the past fifteen years [200][201][202][203][204][205].…”
Section: Structure-activity Relationships and Biological Activities O...mentioning
confidence: 99%